7D.01: ESSENTIAL HYPERTENSION INDUCES EARLY FUNCTIONAL AND STRUCTURAL VASCULAR AGEING IN SMALL RESISTANCE ARTERIES. (June 2015) - Bruno, R.; Duranti, E.; Taddei, S.; Virdis, A.
Abstract : Objective: We evaluated cross-sectionally whether vascular remodeling is physiologically present in normal aging, and whether hypertension causes an acceleration of the aging process for vascular function and structure. Design and method: 40 essential hypertensive patients (EH, age 44.9 ± 13.2 years; blood pressure, BP, 157 ± 8/99 ± 3 mmHg) and 36 normotensive control individuals (Ctrl, age 44.7 ± 12.7 years; BP: 128 ± 7/80 ± 4 mmHg) underwent laparoscopic surgery with subcutaneous adipose tissue biopsy. Small resistance arteries were studied by pressure micromiography. Endothelium-dependent and –independent vasodilation were evaluated by dose-response curve to Acetylcholine (ACh) and sodium nitroprusside (SNP). Maximum %inhibition by L-NAME on response to Ach was calculated. Structural alterations were assessed by media-lumen ratio (M/L). Results: EH showed a reduced vasodilation to Ach (P < 0.001), but not to SNP, compared to Ctrl. In both groups, %inhibition by L-NAME on response to ACh was inversely related to age (EH, r:-0.75; P < 0.0001; Ctrl, r:-0.49; P < 0.0001). NO availability was significantly reduced in EH as compared to Ctrl for each age group (<30 years: 22 ± 6% vs 30 ± 9%, P < 0.05; 31–45 years: 17 ± 3% vs 30 ± 3%, P < 0.0001; 46–60 years: 9 ± 4% vs 21 ± 6%, P < 0.0001; >60 years: 4 ± 3% vs 13 ± 3%, P < 0.05). Age-hypertension interaction (Repeated measures ANOVA) was not significant (p = 0.25). EH showed an increased M/L (P < 0.001) compared to Ctrl. In both groups, M/L was positively related to age. (EH, r:0.82; P < 0.0001; Ctrl, r:0.50; P < 0.0001). M/L was similar in EH and Ctrl for individuals < 30 years, but greater in EH than Ctrl for the other age groups (31–45 years: 6.5 ± 0.4% vs 5.6 ± 0.4%, P < 0.0001; 46–60 years: 7.4 ± 0.5% vs 5.8 ± 0.2%, P < 0.0001; >60 years: 7.9 ± 0.3% vs 6.3 ± 0.5%, P < 0.0001). There was a significant age-hypertension interaction (Repeated measures ANOVA p = 0.0009). Conclusions: In small resistance arteries, aging is physiologically characterized by progressive reduction in NO availability and increased M/L. In hypertensive patients, NO availability is early reduced in comparison to Ctrl, but the progression rate with age appears to be similar. Conversely, structural alterations are influenced by hypertension only after 30 years of age, but the progression rate with age is steeper in the presence of hypertension.